The Barbados Emergency Ambulance Service: High Frequency of Nontransported Calls - Phillips, Sherwin E.; Gaskin, Pamela S.; Byer, David; Cadogan, W. L.; Brathwaite, Andrew; Nielsen, Anders L. (Emergency Medicine International, 2012)
Objectives. There are no published studies on the Barbados Emergency Ambulance Service and no assessment of the calls that end in nontransported individuals. We describe reasons for the nontransport of potential clients. Methods. We used the Emergency Medical Dispatch (Medical Priority Dispatch System) instrument, augmented with five local call types, to collect information on types of calls. The calls were categorised under 7 headings. Correlations between call types and response time were calculated. Results. Most calls were from the category medical (54%). Nineteen (19%) percent of calls were in the non-transported category. Calls from call type Cancelled accounted for most of these and this was related to response time, while Refused service was inversely related (P=0.01). Conclusions. The Barbados Ambulance Service is mostly used by people with a known illness and for trauma cases. One-fifth of calls fall into a category where the ambulance is not used often due to cancellation which is related to response time. Other factors such as the use of alternative transport are also important. Further study to identify factors that contribute to the non-transported category of calls is necessary if improvements in service quality are to be made.